ANALISIS SPASIAL TINGKAT BAHAYA TANAH LONGSOR DI KABUPATEN ACEH TENGGARA MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS - Haqul Baramsyah; Keefi Kienan; Deea Rizki Oziana; Pocut Nurul Alam (Jurnal Sains dan Teknologi Reaksi, 2026)
Kabupaten Aceh Tenggara, located within the Leuser Ecosystem, carries a high risk of hydrometeorological disasters. This study aims to map landslide hazard level zonation using the Ministry of Agriculture, Forestry and Fisheries (MAFF)-Japan through Geographic Information System (GIS) platform. The parameters used include rainfall, land use, slope inclination, soil type, geological type, and landform. Analysis was conducted using overlay and scoring techniques. The results show that Southeast Aceh Regency has three hazard level categories: low (7.19% or 306 km²), moderate (89.78% or 3,806 km²), and high (3.03% or 130 km²). Areas with a high hazard level are dominated by forest areas with steep slopes (15%) and high rainfall (3,500 mm/year). This mapping is expected to serve as a foundation for spatial planning policies and disaster mitigation in the region. Key words: Landslides, MAFF-Japan Method, Aceh Tenggara, Geographic Information System, Mitigation